Analyzing Inflation with P – Star Model - Javid Bahrami; Maryam Farshchi (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2010)
This paper presents a test of the P* model using Iran quarterly data over the period 1988-2005. The basic formulation of the P* model, which is derived from the quantity theory of money, is manipulated to obtain an equation for the price gap and level of output and velocity gaps. So the P-Star model implies that inflation is determined by the level of output gap and velocity gap. On the other hand real money gap can either be used instead of price gap, as the other approach. Estimation of the dynamic relation between the inflation rate and price gap are significant and price gap’s share is about 50 percent in inflation process.